Does transformational leadership shape lecturer performance? The mediating role of organizational engagement - Angela, Lia; Herningrum, Indah; Alfian, Muhammad; Asbupel, Fatnan; Lardiman, Hendra (Indonesian Journal of Educational Development (IJED), 2025)
This study investigates the effects of transformational leadership, academic culture, and workload on lecturer performance, with organizational engagement as a mediating variable. Using a quantitative survey of 210 permanent lecturers at Indonesian state Islamic universities and analyzed through SEM (AMOS 24), the study finds that transformational leadership and academic culture positively influence both engagement and performance. At the same time, workload negatively impacts engagement and has no direct effect on performance. Engagement partially mediates the influence of leadership and culture, and fully mediates the effect of workload on performance. These findings emphasize the importance of supportive leadership, strong academic culture, and effective workload management in enhancing lecturer engagement and performance, offering strategic insights for institutional reform in higher education.